The Influence of the Talking Stick Cooperative Learning Model in Science Subjects on the Activeness of Elementary School Students - Sasmithaningrum, Talitha Destiny (research, training and philanthropy institution Natural Aceh, 2024)
There are several students who, when answering questions, especially in the subject of science given by the teacher, still feel embarrassed and fearful. Moreover, it is not only the fear of answering; some students also lack the willingness to express their opinions. Consequently, the teaching and learning activities predominantly employ lecture methods, which may not always align with the subject matter being taught. The objective of this research is to examine the influence of the cooperative learning model, specifically the Talking Stick, on the science learning activities of fifth-grade students. The research design is experimental with a pre-test and post-test group design. The researcher included the entire population of fifth-grade students, totaling 30 students, comprising 15 male and 15 female students, at SDN 1 Krembung. In this study, the researcher used a saturated sampling technique with a sample size of 30 respondents. Data were collected through questionnaires and analyzed using a one-sample t-test. The results of the one-sample t-test indicated a ρ value of 0.00 for both pre-test and post-test results, signifying ρ < α, with α = 0.05. This indicates a difference in students' activity in solving science problems before and after utilizing the Talking Stick model. Based on the group averages, the pre-test average was 56.8, and the post-test group average was 71. Cooperative learning models are developed to achieve student performance, including academic achievement, tolerance, acceptance of diversity, and the enhancement of social skills. The primary goal of cooperative learning is to maximize student performance to improve academic achievement and understanding, both individually and as a group.